Humor dalam Horor: Analisis genre pada film hello ghost dan Kang Mak from Pee Mak - Helenita Margareth br Tarigan; Tutiasri, Ririn Puspita (Universitas Garut, 2025)
Abstract The focus of this research is not only to examine how horror and comedy elements are combined but also how the adaptation process reflects local values familiar to Indonesian audiences. This study aims to analyze the construction of the horror-comedy genre in the films Hello Ghost (2023) and Kang Mak from Pee Mak (2024), which are adaptations of foreign films but successfully adjusted to the Indonesian cultural context. The study applies a descriptive qualitative approach using the Repertoire of Elements method, which covers narrative structure, characterization, setting, iconography, and visual-audio style. In addition, Rick Altman’s genre theory is employed to understand the interaction between text, institutions, and audiences in shaping meaning. The findings reveal that both films present a balanced blend of horror and comedy, though each emphasizes different cultural aspects. Hello Ghost offers emotional horror through personal iconography representing trauma, loss, and the healing process of the protagonist. In contrast, Kang Mak from Pee Mak highlights comical horror derived from local beliefs and symbols such as shamanic rituals, traditional stilt houses, and mystical objects. Comedy in both films is expressed through humorous characterizations, slapstick scenes, dark comedy, and situations of miscommunication that enliven the narrative while reducing tension. In terms of visual and audio style, both films make use of lighting, camera work, and musical scoring to balance frightening moments with humorous relief. This study concludes that the horror-comedy genre in the Indonesian context functions not only as entertainment but also as a medium of reflection on cultural values, family ties, and social trauma. The success of these adaptations demonstrates the dynamic nature of genre, which can be reshaped according to local tastes without losing its global narrative essence. Keywords: Horror comed; Indonesian film; film genre; hello ghost; Kang Mak from Pee Mak. Abstrak Fokus penelitian ini tidak hanya mengkaji bagaimana elemen horor dan komedi digabungkan, tetapi juga bagaimana proses adaptasi tersebut merefleksikan nilai-nilai lokal yang dekat dengan kehidupan masyarakat. Penelitian ini bertujuan untuk menganalisis konstruksi genre horor komedi dalam film Hello Ghost (2023) dan Kang Mak from Pee Mak (2024) yang merupakan bentuk adaptasi film luar negeri namun berhasil disesuaikan dengan konteks budaya Indonesia. Metode penelitian menggunakan pendekatan deskriptif kualitatif dengan analisis Repertoire of Elements yang mencakup unsur naratif, karakterisasi, setting, ikonografi, serta gaya visual dan audio. Selain itu, penelitian memanfaatkan teori genre Rick Altman untuk memahami hubungan antara teks, institusi, dan audiens dalam pembentukan makna. Hasil penelitian menunjukkan bahwa kedua film menampilkan paduan horor dan komedi yang seimbang dengan pendekatan kultural yang berbeda. Hello Ghost menghadirkan horor emosional melalui ikonografi personal yang mewakili trauma, kehilangan, serta proses penyembuhan karakter utama. Sementara itu, Kang Mak from Pee Mak menonjolkan horor komikal yang bersumber dari simbol budaya dan kepercayaan lokal, seperti ritual dukun, rumah panggung, hingga benda mistis. Unsur komedi hadir melalui karakterisasi humoris, adegan slapstick, dark comedy, dan situasi miskomunikasi yang menghidupkan narasi serta mengurangi ketegangan. Dari segi gaya visual dan audio, kedua film memanfaatkan pencahayaan, pengambilan gambar, dan musik untuk menyeimbangkan suasana menakutkan dengan momen humor. Penelitian ini menyimpulkan bahwa genre horor komedi dalam konteks Indonesia berfungsi bukan hanya sebagai hiburan, melainkan juga sebagai media refleksi nilai budaya, kekeluargaan, dan trauma sosial. Keberhasilan adaptasi membuktikan bahwa genre bersifat dinamis dan mampu menyesuaikan diri dengan selera lokal tanpa kehilangan nilai naratif global. Kata-kata kunci: Horor komedi; film Indonesia; genre film; hello ghost; Kang Mak from Pee Mak.